Peak Music Experience and The Replication of Emotions Through Meme : Case Study of Prontaxan in Yogyakarta - Ilham Muammar Shidiq; Oki Rahadianto Sutopo (Universitas Cokroaminoto Palopo, 2022)
This study aims to explore how the aspects of outside social class and economy influence people’s choices in their lives especially their music preference and their perception towards the things affiliated to the music. This study is a qualitative research. The data is collected through observation and in-depth interview. The respondents are four people, two male and two females, with the range of 20-30 years of age. They are from middle social class. The results of the research show life experience determine their preference of music and how they put stance as indie youth in Yogyakarta. Social class of funkot and the informant does not determine their music preference. In the context of the youth who listen to Prontaxan, meme plays a role to mediate the music to the audience. Meme is used as a promotional device as well as an experience that stands out getter. The feelings in their experiences are replicated by meme which later become the resource of Gidden’s self-identity (1991).